Asset price shocks, real expenditures, and financial structure: a multi-country analysis - Robert S. Chirinko; Leo de Haan; Elmer Sterken (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines the responses of private consumption, residential investment, and business investment in 11 EU countries, Japan, and the United States to shocks in housing and equity prices. The effects are assessed with a Structural Vector Auto Regressive (SVAR) model, and four key findings emerge. First, the impacts of asset price shocks are heterogeneous across countries. Second, these heterogeneous responses are systematically related to cross-country variation in financial structure. We are thus able to document the importance of a wealth/balance sheet channel for private consumption and residential investment and an equity finance channel for business investment. Third, for a given country, housing shocks have a much greater impact than equity shocks. Fourth, variance decompositions indicate that monetary policy reacts to equity price shocks but not to housing price shocks. These results highlight the important role played by asset prices on real activity and fuel the debate about the inclusion of asset prices in the formulation of monetary policy.
Keywords: E44; E52; E2; 330; Monetary policy; asset prices; structural VAR; Wohnungsmarkt; Börsenkurs; Schock; VAR-Modell; Geldpolitik; EU-Staaten; USA; Japan